EFFECT OF SPACING AND FERTILIZER LEVELS ON GROWTH AND YIELD OF URDBEAN - N. B. MURADE; D. B. PATIL; H. D. JAGTAP; S. M. MORE (The Bioscan, 2014)
A field experiment was conducted at Pulses Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola during Kharif season of 2011-12 on Blackgramgenotype AKU-07-04. The experiment was laid out in Factorial randomized block design with three replication and eight treatment combinations. The growth character and yield attributes viz, number of leaves, number of branches, leaf area, dry matter, number of pod plant-1, number of grain pod-1and grain yield plant-1 wasrecorded higher under wider spacing (45x10 cm) than closer spacing(30x10 cm). All these character were recorded higher by application of fertilizer level 30:60 kg NP2O5 ha-1 than the fertilizer level of 20:40 kg NP2O5 ha-1but was par with the fertilizer level of 40:80 NP2O5 ha-1. Interaction effect between spacing and fertilizer levels did not influence the growth parameters and yield of Blackgram.